Comparison of Nasopharyngeal Airway with Endoscopic Respiratory Mask for Hypoxemia in Painless Gastrointestinal Endoscopy in Obese Outpatients: Study Protocol for a Randomized Controlled Trial - Xiang D; Deng L; Zhou R; Zhang X; Tian L; Jiang W; Zhou Y; Chen W; Peng Y (Medical Devices: Evidence and Research)
Dongmei Xiang,1,* Lei Deng,2,* Rui Zhou,3– 5 Xianjie Zhang,1 Lei Tian,1 Wencai Jiang,1 Yukai Zhou,1 Wenya Chen,1 Yanhua Peng1 1Department of Anesthesiology, the Deyang People’s Hospital, Deyang City, Sichuan Province, 618000, People’s Republic of China; 2Department of Gastroenterology, the Deyang People’s Hospital, Deyang City, Sichuan Province, 618000, People’s Republic of China; 3Department of Anesthesiology and Perioperative Medicine, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200434, People’s Republic of China; 4Translational Research Institute of Brain and Brain-Like Intelligence, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200434, People’s Republic of China; 5Clinical Research Center for Anesthesiology and Perioperative Medicine, Tongji University, Shanghai, 200434, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanhua Peng, Department of Anesthesiology, the Deyang People’s Hospital, No. 173 section 1 Mount Taishan North Road Jingyang District, Deyang City, Sichuan Province, People’s Republic of China, Email pyhuaa@163.comIntroduction: Sedatives and anesthetics can modify airway tone and induce respiratory depression, exacerbating the gas exchange impairments associated with obesity. In obese patients undergoing gastrointestinal endoscopy, upper airway obstruction and hypoventilation are prevalent, leading to frequent occurrences of hypoxemia during the procedure. This study aims to investigate the effects of the nasopharyngeal airway in mitigating hypoxemia via alleviating upper airway obstruction in obese outpatients during painless gastrointestinal endoscopy procedure.Methods: This is a prospective single-center randomized controlled study. After signing the written informed consent, eligible outpatients scheduled for painless gastrointestinal endoscopy will be randomly allocated into the nasopharyngeal airway group (group N) and control group (group C), with 88 patients in each group. Patients in group N will undergo intubation of the nasopharyngeal airway prior to examination, whereas patients in group C will receive oxygen therapy through an endoscopic respiratory mask at a flow rate of 10 L/min during the procedure. All patients in two groups will receive propofol and opioids for procedural sedation. The primary outcome will be the incidence of hypoxemia. The secondary outcomes will be the incidence of epistaxis, suspended examination due to hypoxemia, manual ventilation, the times of attempt to nasopharynx airway insertion, duration of insertion of nasopharyngeal airway, tracheal/laryngeal mask intubation, adverse cardiovascular events, gastrointestinal complications, VAS score of nasopharynx pain after removing the nasopharyngeal airway, satisfaction score of patients, endoscopist and anesthesiologists.Discussion: This study evaluates the effects of nasopharyngeal airway insertion on hypoxemia caused by procedural sedation in obese patients undergoing gastrointestinal endoscopy. The results of this study are expected to provide evidence for the use of nasopharyngeal airway in obese outpatients.Trial Registration Number: ChiCTR2300078892.Keywords: nasopharyngeal airway, hypoxemia, obese outpatients